EIB Working Paper 2021/05 - The impact of bank loan terms on intangible investment in Europe - Kolevy, Atanas (European Investment Bank, 2021)
Using EIBIS data, this paper investigates the effects of different loan conditions on firms' propensity to invest in intangible assets. When firms face restriction in how much they can borrow, this has a strong effect on how much they invest in intangible assets. Using European firm-level data from the EIB Investment Survey, this paper shows that, by contrast, unfavourable interest rates, maturity and collateral requirements have no significant effects on the probability to invest in intangible assets, provided firms are satisfied with their loan size. These terms however, do have a negative impact on the probability to invest in multiple intangible assets, undermining the ability of firms to benefit from the complementarities of these assets. The paper documents the effect of loan conditions on investment intensity, as well. The effect of quantity rationing on the amount invested in intangible assets is found to be limited. Other loan conditions however, like cost, maturity and collateral requirements, have significant effect on investment intensity.